Identification and analytical characterization of four synthetic cannabinoids ADB‐BICA, NNL‐1, NNL‐2, and PPA(N)‐2201. Issue 1 (30th May 2016) - Qian, Zhenhua; Jia, Wei; Li, Tao; Hua, Zhendong; Liu, Cuimei
Abstract : Since the first appearance as psychotropic drugs in illegal markets in 2008, the spread of synthetic cannabinoids is becoming a serious problem in many countries. This paper reports on the analytical properties and structure elucidation of four cannabimimetic derivatives in seized material: 1‐benzyl‐ N ‐(1‐carbamoyl‐2, 2‐dimethylpropan‐1‐yl)‐1 H ‐indole‐3‐carboxamide (ADB‐BICA, 1 ), N ‐(1‐carbamoylpropan‐1‐yl)‐1‐(5‐fluoropentyl)‐1 H ‐pyrrolo[2, 3‐b]pyridine‐3‐carboxamide (NNL‐1, 2 ), (4‐benzylpiperazin‐1‐yl)(1‐(5‐fluoropentyl)‐1 H ‐indol‐3‐yl)methanone (NNL‐2, 3 ), and N ‐(1‐carbamoyl‐2‐phenylethyl)‐1‐(5‐fluoropentyl)‐1 H ‐indazole‐3‐carboxamide (PPA(N)‐2201, 4) . The identifications were based on liquid chromatography‐quadrupole‐time‐of‐flight‐mass spectrometry (LC‐QTOF‐MS), gas chromatography‐mass spectrometry (GC‐MS), Fourier transform infrared spectroscopy (FT‐IR), and nuclear magnetic resonance (NMR) spectroscopy. No chemical or pharmacological data about compounds1–3 have appeared until now, making this the first report on these compounds. The GC‐MS data of4 has been reported, but this study added the LC‐MS, FT‐IR, and NMR data for additional characterization. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Four synthetic cannabinoids ADB‐BICA, NNL‐1, NNL‐2, and PPA (N)‐2201were identified using LC‐QTOF‐MS, GC‐MS, FT‐IR, and NMR